2022
DOI: 10.3389/fcvm.2022.839441
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-Induced Multi-Systemic Toxicity Involving the Liver, Lungs, Thyroid, and Eyes: A Case Report

Abstract: ObjectivesAmiodarone is widely used to treat arrhythmia. However, amiodarone is known for its severe toxicity to the liver, lungs, and thyroid. Amiodarone causes liver damage ranging from asymptomatic serum aminotransferase elevation to hepatic failure requiring liver transplantation. Although amiodarone toxicity has been reported, its simultaneous multi-organ toxicity is not well-known. Here, we introduce a novel case of multi-systemic amiodarone toxicity involving the liver, lungs, thyroid, and eyes.Case Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, despite the quick discontinuation of amiodarone and the use of intravenous pulsed methylprednisolone at high doses, it did not provide any rapid therapeutic relief or positive response as suggested commonly in literature. 4,10,15,16 These factors have all contributed to the rapidity and severity of APT in this patient. Though not previously highlighted in literature for the cut off for reversible versus non-reversible drug induced interstitial lung disease, it could be considered that this patient's APT may very well have been past that of a reversible stage.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, despite the quick discontinuation of amiodarone and the use of intravenous pulsed methylprednisolone at high doses, it did not provide any rapid therapeutic relief or positive response as suggested commonly in literature. 4,10,15,16 These factors have all contributed to the rapidity and severity of APT in this patient. Though not previously highlighted in literature for the cut off for reversible versus non-reversible drug induced interstitial lung disease, it could be considered that this patient's APT may very well have been past that of a reversible stage.…”
Section: Discussionmentioning
confidence: 79%
“…It has an iodine containing compound, known as an iodinated benzofuran derivative, which is highly lipophilic, hence can accumulate in fat containing tissues and different organs such as lungs, liver, thyroid, eyes, and heart – mainly highly perfused organs. 1 , 3 , 4 However, pulmonary toxicity is the most serious of all these complications of amiodarone use. 2 , 5 , 6 Though it may occur with any dosage, the likelihood of pulmonary toxicity does decrease with lower doses of amiodarone.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 24% of patients taking amiodarone had asymptomatic elevated serum aminotransferase levels. In various studies, less than 1% of patients reported the development of significant drug-induced liver injury, ranging from symptomatic hepatitis and micronodular cirrhosis to liver failure requiring liver transplantation [ 9 ]. Acute hepatocellular injury occurred within 24 hours after the administration of intravenous amiodarone [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver function should be checked in people treated with this drug As previously mentioned, amiodarone is a lipophilic drug which can accumulate in the liver causing amiodaroneinduced liver disease, histologically similar to alcoholic and no-alcoholic steatohepatitis [15]. Amiodarone causes liver damage, ranging from asymptomatic increases in serum transaminases to liver failure requiring liver transplant [16]. Patients infected with the hepatitis B and C viruses are at high risk of developing cirrhosis.…”
Section: Discussionmentioning
confidence: 99%